Circ_0000471 suppresses the progression of ovarian cancer through mediating mir‐135b‐5p/dusp5 axis. (13th February 2023) - Yu, Shanshan; Yu, Maowen; Chen, Jianjun; Tang, Hongbo; Gong, Wuqing; Tan, Hui
Abstract: Background: Ovarian cancer (OC) is a common gynecologic cancer with high incidence and mortality. We attempted to investigate the role of circular RNA_0000471 (circ_0000471) in OC progression and its associated mechanism. Methods: Reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR) and western blot assay were conducted to measure RNA and protein expression, respectively. Cell proliferation was analyzed by Cell Counting Kit‐8 (CCK8) assay, colony formation assay, and 5‐Ethynyl‐2′‐deoxyuridine (EdU) assay. Cell apoptosis was assessed by flow cytometry. Cell migration and invasion were analyzed by wound healing assay and transwell assay, respectively. Dual‐luciferase reporter assay and RNA immunoprecipitation (RIP) assay were conducted to verify the target relationships. Xenograft tumor model was established to assess the role of circ_0000471 on tumor growth in vivo. Results: Circ_0000471 expression was down‐regulated in OC tissues and cell lines. Circ_0000471 overexpression blocked the proliferation, migration, and invasion and triggered the apoptosis of OC cells. Circ_0000471 served as a molecular sponge for microRNA‐135b‐5p (miR‐135b‐5p), and circ_0000471 overexpression‐mediated anti‐tumor influences in OC cells were largely reversed by the overexpression of miR‐135b‐5p. Dual specificity phosphatase 5 (DUSP5) was a target of miR‐135b‐5p, and miR‐135b‐5p silencing‐induced anti‐tumor effects were largely counteracted by the interference of DUSP5. Circ_0000471 increased DUSP5 expression by sponging miR‐135b‐5p in OC cells. Circ_0000471 overexpression restrained the growth of xenograft tumors in vivo. Conclusion: Overexpression of circ_0000471 inhibited OC development by targeting miR‐135b‐5p/DUSP5 axis, indicating that circ_0000471 may be a new potential target for OC treatment.